2016
DOI: 10.3390/catal6090131
|View full text |Cite
|
Sign up to set email alerts
|

Support Screening Studies on the Hydrogenation of Levulinic Acid to γ-Valerolactone in Water Using Ru Catalysts

Abstract: γ-Valerolactone (GVL) has been identified as a sustainable platform chemical for the production of carbon-based chemicals. Here we report a screening study on the hydrogenation of levulinic acid (LA) to GVL in water using a wide range of ruthenium supported catalysts in a batch set-up (1 wt. % Ru, 90 • C, 45 bar of H 2 , 2 wt. % catalyst on LA). Eight monometallic catalysts were tested on carbon based(C, carbon nanotubes (CNT)) and inorganic supports (Al 2 O 3 , SiO 2 , TiO 2 , ZrO 2 , Nb 2 O 5 and Beta-12.5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Among the target products, levulinic acid (LA) is the main compound of biomass hydrolysis, which has been classified by the United States Department of Energy as one of the top-12 promising building blocks [7]. LA represents a valuable intermediate for the synthesis of several chemicals for application in fuel additives, fragrances, solvents, pharmaceuticals, and plasticizers [8][9][10][11][12][13]. LA, also known as 3-acetylpropionic acid, 4-oxovaleric acid, or 4-oxopentanoic acid, is a very interesting platform chemical, because of its versatile chemistry, including one carbonyl, one carboxyl and α-H in its inner structure, looking like a short chain and non-volatile fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…Among the target products, levulinic acid (LA) is the main compound of biomass hydrolysis, which has been classified by the United States Department of Energy as one of the top-12 promising building blocks [7]. LA represents a valuable intermediate for the synthesis of several chemicals for application in fuel additives, fragrances, solvents, pharmaceuticals, and plasticizers [8][9][10][11][12][13]. LA, also known as 3-acetylpropionic acid, 4-oxovaleric acid, or 4-oxopentanoic acid, is a very interesting platform chemical, because of its versatile chemistry, including one carbonyl, one carboxyl and α-H in its inner structure, looking like a short chain and non-volatile fatty acid.…”
Section: Introductionmentioning
confidence: 99%
“…The most characteristic literature data on levulinic acid hydrogenation are presented in Table S1 in the Supporting Information. As a rule, hydrogenation of levulinic acid in the presence of heterogeneous Ru catalysts was conducted at 130–200 °C (more rarely at 50–90 °C) and 15–50 bar of hydrogen, using activated carbon, silica, alumina, or titania as carriers and water,, 1,4‐dioxane, and alcohols as solvents . Herein, turnover frequencies (TOFs) reached values mostly of 100–1000 h −1 (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…The support choice was fixed to reduce the complexity of possible variations during the catalyst synthesis procedure. In addition, we have recently shown good catalytic results for Ru on anatase TiO 2 [30]. Perusal of the literature on Ru/TiO 2 catalyzed LA hydrogenation ( Table 1) finally shows that catalyst performance not only depends on support choice and catalyst synthesis parameters, but that a strong dependence on the choice of solvent can also be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some of us reported on a catalyst screening study for LA hydrogenation in water (90°C, 45 bar H 2 ) using a wide range of supported Ru-catalysts (1 wt.% Ru on C, CNT, Al 2 O 3 , TiO 2 , ZrO 2 , Nb 2 O 5 and HBeta-12.5) and again found that TiO 2 (anatase form, A100) performed better than for Ru/ZrO 2 in this solvent [30]. The results listed above thus show the potential of TiO 2 as support for this reaction and an overview of titania-supported Ru catalysts for LA hydrogenation is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation